Artificial Microglia Nanoplatform Loaded With Anti‐RGMa in Acoustic/Magnetic Feld for Recanalization and Neuroprotection in Acute Ischemic Stroke - Ruiqi Cheng; Xiaoqin Luo; Xiaohui Wu; Zijie Wang; Ziqun Chen; Shaoru Zhang; Hongmei Xiao; Jiaju Zhong; Rongrong Zhang; Yang Cao; Xinyue Qin (Advanced Science)
Abstract Ischemic stroke is a leading cause of death and disability worldwide, and the main goals of stroke treatment are to destroy the thrombus to recanalize blood vessels and protect tissue from ischemia/reperfusion injury. However, current recanalization therapies have serious limitations and there are few neuroprotection methods. Hence, an artificial nanoplatform loaded with anti‐Repulsive Guidance Molecule a monoclonal antibody (anti‐RGMa) and coated with microglia membrane (MiCM) is reported for stroke treatment, namely MiCM@PLGA/anti‐RGMa/Fe3O4@PFH (MiCM‐NPs). Tail vein injection of MiCM‐NPs targeted the ischemia‐damaged endothelial cells because of the MiCM, then superparamagnetic iron oxide (Fe3O4) and anti‐RGMa are released after external low‐intensity focused ultrasound (LIFU) exposure. The thrombus is destroyed by LIFU‐induced “liquid‐to‐gas” phase transition and cavitation of perfluorohexane (PFH) as well as Fe3O4 movements induced by an external magnetic field. Anti‐RGMa protected the ischemic region from ischemia/reperfusion injury. The nanoplatform enabled visualization of the thrombus by ultrasound/photoacoustic imaging when the clot is in an extracranial artery. Importantly, in vivo animal studies revealed good safety for MiCM‐NPs treatment. In conclusion, this nanoplatform shows promise as an ischemic stroke treatment strategy combining targeted delivery, recanalization, and neuroprotection.